Analysis Of Marketing Strategy For Multi-Purpose Fund Products Umrah Loan Increasing The Number Of Customers - Saragih, Arif Kusnedi; Syarvina, Wahyu; Indra, Ahmad Perdana (UNIVERSITAS PAKUAN, 2025)
The purpose of this study is to analyze how the marketing strategy of the umrah advance fund product increases the number of customers. This research method uses a descriptive qualitative approach, with data collection techniques through interviews, observations, and documentation. The collected data is then analyzed descriptively qualitatively to identify and group relevant information. The results of this study indicate that PT. Bank Pembiayaan Rakyat Syariah Al-Wasliyah has succeeded in implementing an effective marketing strategy in marketing the umrah advance fund product. Through a marketing mix that includes aspects of product, price, promotion, location, and cross-selling, this bank can attract customers, especially ASN, who want to perform the umrah pilgrimage but are constrained by financial problems. Product advantages, such as ease of payment without penalties and cooperation with quality umrah travel, are the main attractions for customers. Competitive pricing strategies and promotions carried out through word of mouth, distribution of brochures, and a personal selling approach further strengthen the marketing of this product. In conclusion, PT Bank Pembiayaan Rakyat Syariah Al-Wasliyah has succeeded in implementing a marketing strategy by increasing the number of customers.